Manufacture of construction materials by energy-saving technology through the example of the Bashkir region. Issue 1 (August 2020) - Gabitov, A I; Ryazanova, V A; Salov, A S; Gaisin, A M; Timofeev, A A
Abstract: Information on the history and formation of the production and application of efficient concrete walling items and road facilities in the construction practice is presented herein by studying historical data. Ways to improve quality of small walling items and road facilities to comply with current energy-saving requirements are analyzed from the historical point of view. Vibropressed technology became widespread over 40 years ago in North America and Europe, being characterized by high capacity and automation of equipment with abilities to manufacture wide spectrum of products by size, shape, finish and color distinguished by low material and energy intensity of production, efficiency of application thereof in energy-saving wall constructions. Special features in making vibropressed concrete items by Besser equipment in the Bashkortostan construction companies are presented.